Penggunaan AI Dalam Keseharian Untuk Kemudahan Melalui Model UTAUT2: (Studi Literatur) - Judhananto, Muhammad Nadhif; Natanael, Fero; Irwansyah (PT. Kreasi Karya Majakata, 2025)
This study aims to examine the role of technology, particularly artificial intelligence, in modern society. In an era of rapid advancement, technology has become an integral part of how individuals communicate and interact directly. The research method used is a qualitative literature study. This study explores the concept of artificial intelligence through a unified theoretical model that impacts daily life and functions in modern society. The findings indicate that the use of artificial intelligence and the second acceptance theory has become a crucial factor in enhancing convenience and productivity, as well as facilitating various aspects of life. The conclusion of this study highlights the significant role of digital technology as a medium for addressing issues in modern life. This article aims to discuss the use of digital technology in everyday life to achieve convenience. The results show that daily routines have changed due to new adaptations to the use of digital media applied in contemporary society.